Water-based ultra-thin woodware flame-retardant coating as well as preparation method and application thereof
By using water-based ultra-thin wood flame retardant coatings, combined with the catalytic carbonization and adsorption of Fe-MOFs synergists, the complex and time-consuming problems of traditional wood flame retardant treatment and environmental pollution are solved, and an efficient and environmentally friendly flame retardant effect is achieved.
Patent Information
- Application Number
- CN202411821219.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The flame retardant treatment process of traditional wood is complex and time-consuming, and traditional solvent-based wood flame retardant coatings face challenges due to high VOCs emissions and environmental pollution problems.
The preparation materials are made of water-based ultra-thin wood flame retardant coatings, including aqueous acrylic emulsions, flame retardants and Fe-MOFs synergists. The Fe-MOFs material is synthesized by microwaves, has a high specific surface area and a rich pore structure. It can adsorb smoke cores, smoke particles and toxic and harmful gases generated during combustion, and form a dense carbon layer through catalytic carbonization.
It has achieved rapid formation of barrier layers in high temperature environments, effectively curbing fires, and the ultra-thin coating design greatly reduces the amount of coatings, meeting the needs of modern industry and construction for lightweight, efficient and environmental protection.
Smart Images

Figure BDA0005183147970000141 
Figure BDA0005183147970000151 
Figure BDA0005183147970000161
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a water-based ultra-thin wood flame-retardant coating and a preparation method and application thereof. Background Art
[0002] Wood, as a renewable natural material, is favored for its unique properties and wide range of applications. Compared with traditional concrete and metal materials, wood exhibits exquisite finishing effects and the advantages of cleanliness and environmental protection. In addition, wood has been widely used in many fields such as furniture, construction and interior decoration due to its excellent visual, tactile, auditory, olfactory properties and regulatory functions. However, the flammability of wood has become a major limitation to its widespread application, and it also poses a potential threat to people's lives and property safety. The traditional wood flame retardant treatment process is complicated and time-consuming, and usually requires the wood to be fully or partially immersed in a flame retardant to ensure that the flame retardant ingredients penetrate deep into the wood fibers, thereby improving its flame retardant properties. Subsequently, an additional layer of coating is required to enhance the protection and durability of the surface. This process is not only inefficient, but may also weaken the natural charm and visual beauty of the wood. In addition, with the increasing awareness of environmental protection and increasingly stringent regulations, traditional solvent-based wood flame retardant coatings face challenges due to their high VOCs emissions and environmental pollution. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a water-based ultra-thin wood flame retardant coating. The coating not only has excellent flame retardant properties and can quickly form a barrier layer under high temperature environment to effectively contain the fire, but also its ultra-thin coating design greatly reduces the amount of coating used, meeting the urgent needs of modern industry and construction fields for lightweight, high efficiency and environmental protection.
[0004] The invention also provides a method for preparing the water-based ultra-thin wood flame-retardant coating.
[0005] The invention also proposes the application of the water-based ultra-thin wood flame-retardant coating in the field of decoration.
[0006] According to one aspect of the present invention, a water-based ultra-thin wood flame-retardant coating is provided, and the raw materials for preparation include: water-based acrylic emulsion, flame retardant and Fe-MOFs synergist;
[0007] The raw materials for preparing the Fe-MOFs synergist include: metal iron salt, organic ligand and silane coupling agent.
[0008] The present invention uses Fe-MOFs material as a synergist. Due to the rich metal Fe element, the iron oxide derived from it has excellent catalytic oxidation and catalytic carbonization activity, thereby promoting the ability of the substrate to catalytically form carbon during the degradation process, and obtaining a highly graphitized dense carbon layer. At the same time, Fe-MOFs has a high specific surface area and a rich pore structure that can adsorb smoke cores, smoke particles, and toxic and harmful gases generated by the material during the combustion process.
[0009] The present invention adopts a silane coupling agent to modify the Fe-MOFs material, thereby improving the compatibility and dispersibility thereof, and at the same time, through the synergistic flame retardancy of silicon, the flame retardant performance is improved.
[0010] The water-based ultra-thin wood flame-retardant coating prepared by the method of the present invention has good adhesion, impact resistance, flexibility, water resistance, heat resistance and excellent fire retardant performance.
[0011] In some embodiments of the present invention, the flame retardant includes a phosphorus-based flame retardant or a phosphorus-nitrogen-based flame retardant.
[0012] In some embodiments of the present invention, the silane coupling agent includes an aminosilane coupling agent.
[0013] Silane coupling agents are a class of substances with an amphiphilic structure. Some of the groups in their molecules can react with chemical groups on the surface of inorganic substances to form a strong chemical bond, while the other groups have an affinity for organic substances and can react or physically entangle with organic molecules, thereby firmly combining two materials with different properties, thereby improving their dispersibility, compatibility and interface interaction. In addition, the combustion of silane coupling agents generates a dense and stable silicon-containing (main component SiO2) carbon layer, which not only prevents the escape of combustible substances that are burned and decomposed, but also plays a role in heat insulation and oxygen isolation, preventing the thermal decomposition of polymer materials, and achieving the purpose of flame retardancy, low smoke and low toxicity.
[0014] In some embodiments of the present invention, the aminosilane coupling agent includes at least one of KH550 and KH792.
[0015] In some embodiments of the present invention, the raw materials for preparation include, by weight: 45-70 parts of aqueous acrylic emulsion, 20-35 parts of flame retardant and 2-6 parts of Fe-MOFs synergist.
[0016] In some embodiments of the present invention, the prepared raw materials further include: expanded perlite.
[0017] On the one hand, the Fe-MOFs synergist modified by silane coupling agent can not only form covalent bonds through the reaction of silane groups with the hydroxyl groups on the surface of expanded perlite, but also the nitrogen functional groups in the aminosilane coupling agent can form chemical bonds with the surface hydroxyl groups (-OH) and iron ions (Fe3+) of Fe-MOFs. Since Fe-MOFs have rich pore structures and high specific surface areas, the aminosilane coupling agent can be more evenly distributed and form a larger range of chemical bonds with the surface of expanded perlite. At the same time, the long-chain molecular structural unit at the other end of the aminosilane coupling agent can be chemically cross-linked or physically entangled with the polymer molecules, which ultimately significantly improves the compatibility and dispersibility of Fe-MOFs and expanded perlite with polymers.
[0018] On the other hand, MIL-101(Fe) has strong adsorption capacity and high specific surface area. When MIL-101(Fe) is covered on the surface of expanded perlite, during the heating process, MIL-101(Fe) coated on the surface of expanded perlite will release the adsorbed moisture or other volatile gases to provide more expansion power for the expanded perlite, promoting the expanded perlite to expand faster at a relatively low temperature. The coating made of this as raw material can quickly form a barrier layer in a high temperature environment, effectively curb the fire, and realize the design of ultra-thin coating.
[0019] On the other hand, due to the catalytic graphitization of Fe-MOFs and the rapid expansion of expanded perlite, an expanded and dense flame-retardant carbon layer is formed, which can effectively prevent the transfer of heat and oxygen, achieving the purpose of flame retardancy and heat insulation.
[0020] In some embodiments of the present invention, the preparation of raw materials further includes: auxiliary agents.
[0021] In some embodiments of the present invention, the auxiliary agent includes: a film-forming auxiliary agent, a defoaming agent, a thickener and a wetting agent.
[0022] In some embodiments of the present invention, the film-forming aid includes at least one of propylene glycol methyl ether PM, propylene glycol butyl ether PnB, dipropylene glycol methyl ether DPM and dipropylene glycol butyl ether DPnB.
[0023] In some embodiments of the present invention, the defoaming agent includes at least one of TEGO-800, TEGO805, TEGO-810, TEGO-815, TEGO-825, BYK-019 and BYK-020.
[0024] In some embodiments of the present invention, the thickener includes at least one of a nonionic polyurethane associative thickener RM-8W, a hydrophobically modified alkali-swellable associative thickener TT-935, an alkali-swellable non-associative thickener ASE-60, and nonionic associative thickeners TEGO ViscoPlus 3000, TEGO ViscoPlus 3030, and TEGO ViscoPlus 3060.
[0025] In some embodiments of the present invention, the wetting agent is at least one of polyether siloxane copolymer TEGO-245, nonionic organic surfactant TEGO-500, and polyether modified polysiloxane solution BYK-346.
[0026] In some embodiments of the present invention, the raw materials include, by weight: 45-70 parts of aqueous acrylic emulsion, 20-35 parts of flame retardant, 2-6 parts of Fe-MOFs synergist, 2-6 parts of film-forming aid, 0.1-0.3 parts of defoamer, 0.1-1 parts of thickener and 0.1-0.5 parts of wetting agent.
[0027] In some embodiments of the present invention, the raw materials for preparation further include water, by weight.
[0028] According to a second aspect of the present invention, a method for preparing a water-based ultra-thin flame-retardant coating for wood is provided, comprising: mixing and reacting raw materials for preparing the water-based ultra-thin flame-retardant coating for wood.
[0029] In some embodiments of the present invention, the preparation method of the Fe-MOFs synergist comprises:
[0030] A1. dispersing the metal iron salt and the organic ligand and subjecting them to a first microwave heating reaction to obtain a Fe-MOFs material;
[0031] A2. After dispersing the Fe-MOFs material and the silane coupling agent, subjecting the dispersed Fe-MOFs material and the silane coupling agent to a second microwave heating reaction to obtain a Fe-MOFs synergist.
[0032] In some embodiments of the present invention, the molar ratio of the metal iron salt to the organic ligand is 3 to 5:3.
[0033] In some embodiments of the present invention, in step A1, the dispersing step further comprises adding a solvent.
[0034] In some embodiments of the present invention, the molar ratio of the metal iron salt, the organic ligand and the solvent is 3-5:3:200-400.
[0035] In some embodiments of the present invention, the temperature of the first microwave heating reaction is 110-160°C.
[0036] In some embodiments of the present invention, the first microwave heating reaction time is 20 to 180 minutes.
[0037] The microwave method for synthesizing MOF has the characteristics of fast reaction speed and small size of synthesized crystals. Microwaves, a fast and uniform heating method, are conducive to generation. Because the shorter reaction time and uniform temperature distribution reduce the chance of particle growth, the generated particles can be kept at the nanoscale. Nano-sized MOF materials have many unique properties and application potentials. For example, they have a larger specific surface area and can provide more active sites; at the same time, nano-MOF materials also exhibit good catalytic properties. These can all improve flame retardancy. The microwave-synthesized nano-Fe-MOFs of the present invention can significantly improve flame retardancy. Only a very small amount (≤6%) of nano-Fe-MOFs needs to be added to significantly reduce the combustion performance of the material while improving its strength and toughness.
[0038] According to a third aspect of the present invention, application of water-based ultra-thin wood flame-retardant coating in the field of decoration is proposed. DETAILED DESCRIPTION
[0039] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0040] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0041] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0042] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0043] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0044] The first aspect of the present invention provides a water-based ultra-thin wood flame-retardant coating, the preparation raw materials include: water-based acrylic emulsion, flame retardant and Fe-MOFs synergist;
[0045] The raw materials for preparing the Fe-MOFs synergist include: metal iron salt, organic ligand and silane coupling agent.
[0046] The embodiment uses Fe-MOFs material as a synergist. Due to the rich metal Fe element, the iron oxide derived from it has excellent catalytic oxidation and catalytic carbonization activity, thereby promoting the ability of the substrate to catalytically form carbon during the degradation process, and obtaining a highly graphitized dense carbon layer. At the same time, Fe-MOFs has a high specific surface area and a rich pore structure that can adsorb smoke cores, smoke particles, and toxic and harmful gases generated during the combustion process of the material.
[0047] In the embodiment, the silane coupling agent is a kind of substance with an amphiphilic structure, a part of the groups in their molecules can react with the chemical groups on the surface of inorganic substances to form a strong chemical bond, and the other part of the groups have the property of being organic-friendly and can react or physically entangle with organic molecules, thereby firmly combining two materials with different properties, thereby improving their dispersibility, compatibility and interface interaction. In addition, the silane coupling agent burns to form a dense and stable silicon-containing (main component SiO2) carbon layer, which not only prevents the escape of combustible substances decomposed by combustion, but also plays a role in heat insulation and oxygen isolation, preventing the thermal decomposition of polymer materials, and achieving the purpose of flame retardancy, low smoke and low toxicity.
[0048] A second aspect of the present invention provides a method for preparing a water-based ultra-thin flame-retardant coating for wood, comprising: mixing and reacting raw materials for preparing the water-based ultra-thin flame-retardant coating for wood.
[0049] In some embodiments of the present invention, the preparation method of the Fe-MOFs synergist comprises:
[0050] A1. dispersing the metal iron salt and the organic ligand and subjecting them to a first microwave heating reaction to obtain a Fe-MOFs material;
[0051] A2. After dispersing the Fe-MOFs material and the silane coupling agent, subjecting the dispersed Fe-MOFs material and the silane coupling agent to a second microwave heating reaction to obtain a Fe-MOFs synergist.
[0052] The microwave method for synthesizing MOF has the characteristics of fast reaction speed and small size of synthesized crystals. Microwaves, a fast and uniform heating method, are conducive to generation. Because the shorter reaction time and uniform temperature distribution reduce the chance of particle growth, the generated particles can be kept at the nanoscale. Nano-sized MOF materials have many unique properties and application potentials. For example, they have a larger specific surface area and can provide more active sites; at the same time, nano-MOF materials also exhibit good catalytic properties. These can all improve flame retardancy. The microwave-synthesized nano-Fe-MOFs of the present invention can significantly improve flame retardancy. Only a very small amount (≤6%) of nano-Fe-MOFs needs to be added to significantly reduce the combustion performance of the material while improving its strength and toughness.
[0053] The third aspect of the present invention provides the use of water-based ultra-thin wood flame-retardant coating in the field of decoration.
[0054] Example 1
[0055] This embodiment provides a water-based ultra-thin wood flame retardant coating:
[0056] The following components are included by weight: 65 parts of water-based acrylic emulsion, 5 parts of FR-125 flame retardant, 20 parts of FT-6501 flame retardant, 5 parts of MIL-101 (Fe) synergist, 3 parts of propylene glycol butyl ether film-forming aid, 0.1 parts of TEGO-815 defoamer, 0.3 parts of TT-935 thickener, 0.2 parts of TEGO-500 wetting agent and 1.4 parts of deionized water;
[0057] This embodiment also provides a method for preparing a water-based ultra-thin wood flame-retardant coating:
[0058] The synergist and the flame retardant are sequentially added into the water-based acrylic emulsion, and then the film-forming aid, the defoamer, the thickener and the wetting agent are sequentially added, dispersed for 10-30 minutes, and the material is filtered to obtain a water-based ultra-thin wood flame retardant coating.
[0059] The preparation method of the MIL-101 (Fe) synergist is as follows: the metal iron salt FeCl3·6H2O, the organic ligand terephthalic acid (H2BDC) and the phytic acid are respectively added to a microwave reactor containing a solvent dimethylformamide (DMF), wherein the molar ratio of FeCl3·6H2O, H2BDC, phytic acid and DMF is 4:2:1:320, and then the reaction is magnetically stirred for 20 minutes, and the reaction is carried out at 110°C for 1 hour and then cooled to room temperature, and then the reaction product is centrifuged, washed with ethanol, and vacuum dried in sequence to obtain the MIL-101 (Fe) material. Subsequently, the MIL-101 (Fe) material and the silane coupling agent KH550 are added to a 90% ethanol aqueous solution, wherein the mass ratio of MIL-101 (Fe), KH550 and the ethanol aqueous solution is 1:2:30, and the reaction is carried out at 50°C for 30 minutes and then centrifuged and dried to obtain the MIL-101 (Fe) synergist.
[0060] Example 2
[0061] This embodiment provides a water-based ultra-thin wood flame retardant coating:
[0062] The following components are included by weight: 70 parts of water-based acrylic emulsion, 22 parts of FT-6500F flame retardant, 3 parts of MIL-100 (Fe) synergist, 3 parts of propylene glycol butyl ether film-forming aid, 0.1 parts of TEGO-815 defoamer, 0.3 parts of TT-935 thickener, 0.2 parts of TEGO-500 wetting agent and 1.4 parts of deionized water;
[0063] This embodiment also provides a method for preparing a water-based ultra-thin wood flame-retardant coating:
[0064] The synergist and the flame retardant are sequentially added into the water-based acrylic emulsion, and then the film-forming aid, the defoamer, the thickener and the wetting agent are sequentially added, dispersed for 10-30 minutes, and the material is filtered to obtain a water-based ultra-thin wood flame retardant coating.
[0065] The metal iron salt Fe(NO3)3.9H2O, the organic ligand trimesic acid (H3BTC) and phytic acid are respectively added to a microwave reactor filled with deionized water, wherein the molar ratio of Fe(NO3)3.9H2O, H3BTC, phytic acid and H2O is 3:2:1:300, then magnetically stirred for 20 minutes, microwaved at 150°C for 1 hour and cooled to room temperature, and then the reaction product is centrifuged, washed with ethanol, and vacuum dried in sequence to obtain MIL-100(Fe) material. Subsequently, the MIL-100(Fe) material and the silane coupling agent KH550 are added to a 90% ethanol aqueous solution, wherein the mass ratio of MIL-100(Fe), KH550 and the ethanol aqueous solution is 1:2:30, microwaved at 50°C for 30 minutes and centrifuged and dried to obtain the MIL-100(Fe) synergist.
[0066] Example 3
[0067] This embodiment provides a water-based ultra-thin wood flame retardant coating:
[0068] The following components are included by weight: 65 parts of water-based acrylic emulsion, 22 parts of TZ-600C flame retardant, 4 parts of AP435 flame retardant, 3 parts of MIL-101 (Fe) synergist, 2 parts of propylene glycol butyl ether film-forming aid, 0.3 parts of TEGO-815 defoamer, 0.2 parts of TT-935 thickener, 0.2 parts of TEGO-500 wetting agent and 3.3 parts of deionized water;
[0069] This embodiment also provides a method for preparing a water-based ultra-thin wood flame-retardant coating:
[0070] The synergist and the flame retardant are sequentially added into the water-based acrylic emulsion, and then the film-forming aid, the defoamer, the thickener and the wetting agent are sequentially added, dispersed for 10-30 minutes, and the material is filtered to obtain a water-based ultra-thin wood flame retardant coating.
[0071] The preparation method of the MIL-101 (Fe) synergist is as follows: the metal iron salt FeCl3·6H2O, the organic ligand terephthalic acid (H2BDC) and the phytic acid are respectively added to a microwave reactor containing a solvent dimethylformamide (DMF), wherein the molar ratio of FeCl3·6H2O, H2BDC, phytic acid and DMF is 4:2:1:320, and then the reaction is magnetically stirred for 20 minutes, and the reaction is carried out at 110°C for 1 hour and then cooled to room temperature, and then the reaction product is centrifuged, washed with ethanol, and vacuum dried in sequence to obtain the MIL-101 (Fe) material. Subsequently, the MIL-101 (Fe) material and the silane coupling agent KH550 are added to a 90% ethanol aqueous solution, wherein the mass ratio of MIL-101 (Fe), KH550 and the ethanol aqueous solution is 1:2:30, and the reaction is carried out at 50°C for 30 minutes and then centrifuged and dried to obtain the MIL-101 (Fe) synergist.
[0072] Example 4
[0073] This embodiment provides a water-based ultra-thin wood flame retardant coating:
[0074] The following components are included by weight: 65 parts of water-based acrylic emulsion, 22 parts of TZ-600C flame retardant, 4 parts of AP435 flame retardant, 3 parts of MIL-101 (Fe) synergist, 5 parts of expanded perlite, 2 parts of propylene glycol butyl ether film-forming aid, 0.3 parts of TEGO-815 defoamer, 0.2 parts of TT-935 thickener, 0.2 parts of TEGO-500 wetting agent and 3.3 parts of deionized water;
[0075] This embodiment also provides a method for preparing a water-based ultra-thin wood flame-retardant coating:
[0076] S1. The synergist, expanded perlite and deionized water were mixed and dispersed at 30 Hz and 150 W for 8 min to obtain a mixture;
[0077] S2. Slowly add the mixture into the water-based acrylic emulsion, and then add the film-forming aid, defoaming agent, thickener and wetting agent in sequence, disperse for 10-30 minutes, filter the material, and obtain a water-based ultra-thin wood flame-retardant coating.
[0078] The preparation method of the MIL-101 (Fe) synergist is as follows: the metal iron salt FeCl3·6H2O, the organic ligand terephthalic acid (H2BDC) and the phytic acid are respectively added to a microwave reactor containing a solvent dimethylformamide (DMF), wherein the molar ratio of FeCl3·6H2O, H2BDC, phytic acid and DMF is 4:2:1:320, and then the reaction is magnetically stirred for 20 minutes, and the reaction is carried out at 110°C for 1 hour and then cooled to room temperature, and then the reaction product is centrifuged, washed with ethanol, and vacuum dried in sequence to obtain the MIL-101 (Fe) material. Subsequently, the MIL-101 (Fe) material and the silane coupling agent KH550 are added to a 90% ethanol aqueous solution, wherein the mass ratio of MIL-101 (Fe), KH550 and the ethanol aqueous solution is 1:2:30, and the reaction is carried out at 50°C for 30 minutes and then centrifuged and dried to obtain the MIL-101 (Fe) synergist.
[0079] Example 5
[0080] This embodiment provides a water-based ultra-thin wood flame-retardant coating. The difference between this embodiment and embodiment 4 is that 3-mercaptopropyltriethoxysilane is used to replace KH550 in embodiment 4, and the other conditions are the same:
[0081] The following components are included by weight: 65 parts of water-based acrylic emulsion, 22 parts of TZ-600C flame retardant, 4 parts of AP435 flame retardant, 3 parts of MIL-101 (Fe) synergist, 5 parts of expanded perlite, 2 parts of propylene glycol butyl ether film-forming aid, 0.3 parts of TEGO-815 defoamer, 0.2 parts of TT-935 thickener, 0.2 parts of TEGO-500 wetting agent and 3.3 parts of deionized water;
[0082] This embodiment also provides a method for preparing a water-based ultra-thin wood flame-retardant coating:
[0083] S1. The synergist, expanded perlite and deionized water were mixed and dispersed at 30 Hz and 150 W for 8 min to obtain a mixture;
[0084] S2. Slowly add the mixture into the water-based acrylic emulsion, and then add the film-forming aid, defoaming agent, thickener and wetting agent in sequence, disperse for 10-30 minutes, filter the material, and obtain a water-based ultra-thin wood flame-retardant coating.
[0085] The preparation method of the MIL-101 (Fe) synergist is as follows: the metal iron salt FeCl3·6H2O, the organic ligand terephthalic acid (H2BDC) and the phytic acid are respectively added to a microwave reactor containing a solvent dimethylformamide (DMF), wherein the molar ratio of FeCl3·6H2O, H2BDC, phytic acid and DMF is 4:2:1:320, and then the reaction is carried out under magnetic stirring for 20 minutes, and the reaction is carried out under microwave at 110°C for 1 hour and then cooled to room temperature, and then the reaction product is centrifuged, washed with ethanol, and vacuum dried in sequence to obtain the MIL-101 (Fe) material. Subsequently, the MIL-101 (Fe) material and 3-mercaptopropyltriethoxysilane are added to a 90% ethanol aqueous solution, wherein the mass ratio of MIL-101 (Fe), 3-mercaptopropyltriethoxysilane and ethanol aqueous solution is 1:2:30, and the reaction is carried out under microwave at 50°C for 30 minutes and then centrifuged and dried to obtain the MIL-101 (Fe) synergist.
[0086] Comparative Example 1
[0087] This comparative example provides a water-based ultra-thin wood flame-retardant coating and a preparation method thereof, specifically:
[0088] A water-based ultra-thin flame-retardant coating for wood comprises the following components by weight: 65 parts of water-based acrylic emulsion, 5 parts of FR-125 flame retardant, 20 parts of FT-6501 flame retardant, 3 parts of propylene glycol butyl ether film-forming aid, 0.1 parts of TEGO-815 defoamer, 0.3 parts of TT-935 thickener, 0.2 parts of TEGO-500 wetting agent and 6.4 parts of deionized water.
[0089] This comparative example also provides a method for preparing a water-based ultra-thin wood flame-retardant coating:
[0090] The flame retardant is added into the water-based acrylic emulsion, and then the film-forming aid, defoamer, thickener and wetting agent are added in sequence, dispersed for 10-30 minutes, and the material is filtered to obtain a water-based ultra-thin wood flame retardant coating.
[0091] Comparative Example 2
[0092] A water-based ultra-thin flame-retardant coating for wood comprises the following components by weight: 70 parts of water-based acrylic emulsion, 22 parts of FT-6500F flame retardant, 3 parts of propylene glycol butyl ether film-forming aid, 0.1 parts of TEGO-815 defoamer, 0.3 parts of TT-935 thickener, 0.2 parts of TEGO-500 wetting agent and 4.4 parts of deionized water.
[0093] Comparative Example 3
[0094] A water-based ultra-thin flame-retardant coating for wood comprises the following components by weight: 65 parts of water-based acrylic emulsion, 22 parts of TZ-600C flame retardant, 4 parts of AP435 flame retardant, 2 parts of propylene glycol butyl ether film-forming aid, 0.3 parts of TEGO-815 defoamer, 0.2 parts of TT-935 thickener, 0.2 parts of TEGO-500 wetting agent and 6.3 parts of deionized water.
[0095] Comparative Example 4
[0096] A water-based ultra-thin flame-retardant coating for wood. The difference between this comparative example and Example 4 is that no silane coupling agent is added, and other conditions are the same.
[0097] This comparative example provides a water-based ultra-thin wood flame retardant coating:
[0098] The following components are included by weight: 65 parts of water-based acrylic emulsion, 22 parts of TZ-600C flame retardant, 4 parts of AP435 flame retardant, 3 parts of MIL-101 (Fe) synergist, 5 parts of expanded perlite, 2 parts of propylene glycol butyl ether film-forming aid, 0.3 parts of TEGO-815 defoamer, 0.2 parts of TT-935 thickener, 0.2 parts of TEGO-500 wetting agent and 3.3 parts of deionized water;
[0099] This comparative example also provides a method for preparing a water-based ultra-thin wood flame-retardant coating:
[0100] S1. The synergist, expanded perlite and deionized water were mixed and dispersed at 30 Hz and 150 W for 8 min to obtain a mixture;
[0101] S2. Slowly add the mixture into the water-based acrylic emulsion, and then add the film-forming aid, defoaming agent, thickener and wetting agent in sequence, disperse for 10-30 minutes, filter the material, and obtain a water-based ultra-thin wood flame-retardant coating.
[0102] The preparation method of the above-mentioned MIL-101 (Fe) enhancer is as follows: metal iron salt FeCl3·6H2O, organic ligand terephthalic acid (H2BDC) and phytic acid are respectively added into a microwave reactor filled with solvent dimethylformamide (DMF), wherein the molar ratio of FeCl3·6H2O, H2BDC, phytic acid and DMF is 4:2:1:320, and then magnetic stirring is performed for 20 minutes, microwave reaction is performed at 110°C for 1 hour, and then cooled to room temperature, and then the reaction product is centrifuged, washed with ethanol, and vacuum dried in sequence to obtain the unmodified MIL-101 (Fe) enhancer.
[0103] Comparative Example 5
[0104] A water-based ultra-thin flame-retardant coating for wood. The difference between this comparative example and Example 1 is that the microwave heating method in Example 1 is replaced by a traditional oven heating method, and other conditions are the same.
[0105] This comparative example provides a water-based ultra-thin wood flame retardant coating:
[0106] The following components are included by weight: 65 parts of water-based acrylic emulsion, 5 parts of FR-125 flame retardant, 20 parts of FT-6501 flame retardant, 5 parts of MIL-101 (Fe) synergist, 3 parts of propylene glycol butyl ether film-forming aid, 0.1 parts of TEGO-815 defoamer, 0.3 parts of TT-935 thickener, 0.2 parts of TEGO-500 wetting agent and 1.4 parts of deionized water;
[0107] This embodiment also provides a method for preparing a water-based ultra-thin wood flame-retardant coating:
[0108] The synergist and the flame retardant are sequentially added into the water-based acrylic emulsion, and then the film-forming aid, the defoamer, the thickener and the wetting agent are sequentially added, dispersed for 10-30 minutes, and the material is filtered to obtain a water-based ultra-thin wood flame retardant coating.
[0109] The preparation method of the above-mentioned MIL-101 (Fe) synergist is as follows: the metal iron salt FeCl3·6H2O, the organic ligand terephthalic acid (H2BDC) and the phytic acid are respectively added into a microwave reactor containing the solvent dimethylformamide (DMF), wherein the molar ratio of FeCl3·6H2O, H2BDC, phytic acid and DMF is 4:2:1:320, then magnetic stirring for 20 minutes, reacting in an oven at 110°C for 20 hours and then cooling to room temperature, and then the reaction product is centrifuged, washed with ethanol, and vacuum dried in sequence to obtain the MIL-101 (Fe) material. Subsequently, the MIL-101 (Fe) material and the silane coupling agent KH550 are added into a 90% ethanol aqueous solution, wherein the mass ratio of MIL-101 (Fe), KH550 and the ethanol aqueous solution is 1:2:30, microwaved at 50°C for 30 minutes and then centrifuged and dried to obtain the MIL-101 (Fe) synergist.
[0110] Test Example 1
[0111] In this test example, the basic properties of the water-based ultra-thin wood flame retardant coatings obtained in the embodiments and comparative examples were tested in accordance with GB / T 12441-2018 "Surface Fire Retardant Coatings". The water resistance, impact resistance, adhesion and flexibility were tested in accordance with GB / T 1733-1993, GB / T1732-2020, GB / T1720-2020 and GB / T1731-2020, respectively. The data results are shown in Table 1.
[0112] Table 1: Basic performance test results of water-based wood flame retardant coatings of Examples and Comparative Examples
[0113]
[0114]
[0115]
[0116] As can be seen from Table 1, the various performance indicators of the water-based ultra-thin wood flame-retardant coatings obtained in Examples 1-5 are within the range required by national standards. The experimental results show that the water-based ultra-thin wood flame-retardant coatings obtained in the present invention meet the flame retardant qualification test of the product and are water-based flame-retardant coatings with excellent performance. By comparing with the control example, it can be seen that the addition of Fe-MOFs synergist can significantly improve its flame retardant properties. Among them, the flame retardant time of Example 3 can reach 36 minutes, which shows that the coating has excellent flame retardant properties, can delay the combustion of the substrate during the heating process, and give full play to its significant role in blocking heat transfer and delaying flame combustion. In Example 4, MIL-101 (Fe) has strong adsorption capacity and high specific surface area. When MIL-101 (Fe) is covered on the surface of expanded perlite, during the heating process, MIL-101 (Fe) coated on the surface of expanded perlite releases the adsorbed moisture or other volatile gases to provide more expansion power for the expanded perlite, promoting the expanded perlite to expand faster at a relatively low temperature. The coating made of this material quickly forms a barrier layer in a high temperature environment, effectively curbing the fire and realizing the design of an ultra-thin coating. The particle structure of expanded perlite and the reinforcing effect of MIL-101 (Fe) can make the coating have better structural stability, increase the mechanical strength and toughness of the coating, effectively reduce the cracking and shedding of the coating when it is impacted by external forces, and improve its impact resistance.
[0117] Test Example 2
[0118] The water-based flame retardant coating obtained in the embodiment and the comparative example is applied on the surface of a 200mmX300mmX5mm wooden board (sample). The sample is sanded in advance to ensure a smooth and flat surface and side edge sealing. After the sample is coated with the coating, it is dried to a constant weight (mass change within 24 hours is not more than 0.5%) at room temperature and natural conditions, and the dry film thickness is about 0.2mm, and then tested. By controlling the valve of the butane spray gun, the total length of the visible flame is 6cm, and the root of the flame is 5cm away from the sample. The sample is directly exposed to the flame of the butane spray gun for 10s for qualitative evaluation. The results are shown in Table 2.
[0119] Table 2: Basic performance test results of water-based wood flame retardant coatings in Example
[0120]
[0121] The results show that the blank wooden board burns rapidly and the flame spreads quickly after contact with the butane flame. After 10 seconds, the flame on the wood surface does not extinguish itself after the butane spray gun is removed. The wooden board coated with the water-based flame retardant coating obtained in Example 3 is not ignited under 10 seconds of flame contact, and the surface carbon layer structure is complete, with an average thickness of 5.2mm, which is much larger than the initial thickness of the coating of 0.2mm. If it continues to contact the butane flame for 10 seconds, the average thickness of the surface carbon layer can reach 10.5mm. Example 4 successfully constructs a flame-retardant carbon layer that is both expanded and dense through the synergistic effect of expanded perlite and Fe-MOFs, while ensuring that the expanded perlite is expanded at a relatively low temperature. This innovative structure can effectively block the transmission path of heat and oxygen, thereby achieving the effect of flame retardancy and heat insulation. The wooden board is not ignited under 10 seconds of flame contact, and the surface carbon layer structure is complete, with an average thickness of 8.2mm, which is much larger than the initial thickness of the coating of 0.2mm. If it continues to contact the butane flame for 10 seconds, the average thickness of the surface carbon layer can reach 13.6mm. The expanded perlite in Example 5 cannot fully expand at high temperatures, and its fire resistance is not as good as that in Example 4.
[0122] The above results all indicate that the water-based ultra-thin wood flame-retardant coating has good adhesion, impact resistance, flexibility, water resistance, heat resistance and excellent fire retardant properties.
[0123] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A water-based ultra-thin flame-retardant coating for wood, characterized in that: The preparation raw materials include: water-based acrylic emulsion, flame retardant and Fe-MOFs synergist; The raw materials for preparing the Fe-MOFs synergist include: metal iron salt, organic ligand and silane coupling agent.
2. The water-based ultra-thin wood flame-retardant coating according to claim 1, characterized in that: The silane coupling agent includes an aminosilane coupling agent.
3. The water-based ultra-thin wood flame-retardant coating according to claim 1, characterized in that: The raw materials for preparation include, by weight: 45-70 parts of water-based acrylic emulsion, 20-35 parts of flame retardant and 2-6 parts of Fe-MOFs synergist.
4. The water-based ultra-thin wood flame-retardant coating according to claim 1, characterized in that: The preparation raw materials also include: expanded perlite.
5. The water-based ultra-thin wood flame-retardant coating according to claim 1, characterized in that: The preparation raw materials also include: auxiliary agents; and / or, the auxiliary agents include: film-forming auxiliary agents, defoaming agents, thickeners and wetting agents.
6. A method for preparing a water-based ultra-thin flame-retardant coating for wood as claimed in any one of claims 1 to 5, characterized in that: include: The raw materials for preparing the water-based ultra-thin wood flame-retardant coating are mixed for reaction.
7. The preparation method according to claim 6, characterized in that: The preparation method of the Fe-MOFs synergist comprises: A1. dispersing the metal iron salt and the organic ligand and subjecting them to a first microwave heating reaction to obtain a Fe-MOFs material; A2. After dispersing the Fe-MOFs material and the silane coupling agent, subjecting the dispersed Fe-MOFs material and the silane coupling agent to a second microwave heating reaction to obtain a Fe-MOFs synergist.
8. The preparation method according to claim 7, characterized in that: The molar ratio of the metal iron salt to the organic ligand is 3 to 5:
3.
9. The preparation method according to claim 7, characterized in that: The temperature of the first microwave heating reaction is 110-160°C.
10. Use of the water-based ultra-thin wood flame-retardant coating according to any one of claims 1 to 5 in the field of decoration.
Citation Information
Patent Citations
Modified MOFs flame retardant, preparation method and application thereof
CN113045762A
Low-shrinkage heat-insulation water-based damping material and preparation method thereof
CN116333538A